Fighting for status : hierarchy and conflict in world politics - Renshon, Jonathan, 1982- (Princeton University Press, 2017)
"There is widespread agreement that status or standing in the international system is a critical element in world politics. The desire for status is recognized as a key factor in nuclear proliferation, the rise of China, and other contemporary foreign policy issues, and has long been implicated in foundational theories of international relations and foreign policy. Despite the consensus that status matters, we lack a basic understanding of status dynamics in international politics. The first book to comprehensively examine this subject, Fighting for Status presents a theory of status dissatisfaction that delves into the nature of prestige in international conflicts and specifies why states want status and how they get it. What actions do status concerns trigger, and what strategies do states use to maximize or salvage their standing? When does status matter, and under what circumstances do concerns over relative position overshadow the myriad other concerns that leaders face? In examining these questions, Jonathan Renshon moves beyond a focus on major powers and shows how different states construct status communities of peer competitors that shift over time as states move up or down, or out, of various groups. Combining innovative network-based statistical analysis, historical case studies, and a lab experiment that uses a sample of real-world political and military leaders, Fighting for Status provides a compelling look at the causes and consequences of status on the global stage."--